Carbohydrate-to-lipid ratio in extruded diets for Nile tilapia farmed in net cages - Coutinho, Juliano José de Oliveira [UNESP]; Neira, Ligia Maria [UNESP]; de Sandre, Lidiane Cristina Gonçalves [UNESP]; da Costa, Jesaias Ismael [UNESP]; Martins, Maria Inez Espagnoli Geraldo [UNESP]; Portella, Maria Célia [UNESP]; Carneiro, Dalton José [UNESP] (Elsevier, 2018)
The study evaluated productive and economic performance, physiological parameters and nutritional efficiency in net cage-reared Nile tilapia fed extruded diets containing four carbohydrate (CHO) and lipid (LIP) ratios. The 1280 fish in the trial were sex-reversed male Nile tilapia from the Gift strain (157.54 ± 3.50 g). Fish were randomly distributed into 16 net cages (1.0 m3), with 80 tilapias per cage. The four practical diets were formulated with the same ingredients at different proportions of starch and soybean oil contained similar digestible protein (251.40 g Kg−1), digestible energy (17.39 Mj Kg−1) and CHO:LIP ratios of: 3.89, 4.87, 6.14 and 7.83 (CHO35/LIP9, CHO39/LIP8, CHO43/LIP7 and CHO47/LIP6, respectively). The diets were provided four times a day, for 120 days. Fish fed a CHO43/LIP7 diet exhibited the best productive performance, with 252.01% percent weight gain (WG), 1.07 ± 0.028% daily specific growth rate (SGR) and 462.08 ± 5.06 g feed intake (FI). Fish fed the CHO43/LIP7 diet also showed the highest gross energy retention efficiency (57.17 ± 4.16%) and LIP use for weight gain (13.71 ± 1.47%). CHO39/LIP8 and CHO43/LIP7 diets produced the best economic performance, with partial net income of US$ 75.27 and US$ 73.40, respectively.
Keywords: Economic cost; Fat; Oreochromis niloticus; Starch